1998
DOI: 10.1002/(sici)1521-4141(199811)28:11<3594::aid-immu3594>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

CD40 induces resistance to TNF-mediated apoptosis in a fibroblast cell line

Abstract: CD40, a member of the TNF receptor family, has been characterized as an important T-B cell interaction molecule. In B cells it co-stimulates isotype switching, proliferation, adhesion and is involved in cell death regulation. In addition to B cells, CD40 expression was found on transformed cells and carcinomas. However, little is known about its functions in these cell types. Recent studies show that CD40 mediates the production of pro-inflammatory cyto-kines in non-hematopoietic cells, inhibits proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 63 publications
1
11
1
Order By: Relevance
“…21 Overexpression of A20 protected HCAECs from CD40-mediated apoptosis. This agrees with previous data by Hess et al 20 demonstrating that A20 protects the fibroblast SV80 cell line against apoptotic cell death induced by TNF. Protection from CD40-mediated apoptosis by A20 could relate to blockade of apoptotic pathways and caspase activation (as shown for TNF and Fas) 22 and/or a decrease in cytokine-induced surface expression of CD40.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…21 Overexpression of A20 protected HCAECs from CD40-mediated apoptosis. This agrees with previous data by Hess et al 20 demonstrating that A20 protects the fibroblast SV80 cell line against apoptotic cell death induced by TNF. Protection from CD40-mediated apoptosis by A20 could relate to blockade of apoptotic pathways and caspase activation (as shown for TNF and Fas) 22 and/or a decrease in cytokine-induced surface expression of CD40.…”
Section: Discussionsupporting
confidence: 93%
“…To the extent that CD40 cross-linking upregulates A20 in a NF-Bdependent manner, one could easily speculate that A20 is part of a regulatory feedback loop modulating signaling through CD40. 19,20 We demonstrate that CD40-mediated signaling of cytokineactivated HCAECs leads to apoptosis contrasting with data in HUVECs. 21 Overexpression of A20 protected HCAECs from CD40-mediated apoptosis.…”
Section: Discussioncontrasting
confidence: 61%
“…Further investigation is underway to explore this resistance in greater detail, and we will be focusing on two anti-apoptotic factors that are strongly or selectively induced by IL13-PE in Th2-type fibroblasts: APRIL 62 and CD40. 63 APRIL confers protection from TRAIL-induced apoptosis whereas CD40 confers protection from tumor necrosis factor-␣-and Fas-induced apoptosis. 63,64 Our previous studies of untreated Th2-type fibroblasts have revealed that the surface expression of CD40 is 100-fold higher on these cells compared with that expressed on normal and Th1-type fibroblasts (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of CD40 signalling in non-immune cell types are not fully understood. However, several reports indicate that signalling through the CD40 receptor can induce survival [25,26] or growth inhibition and enhances apoptosis of various non-immune cell types [27,28].…”
Section: Introductionmentioning
confidence: 99%